Health of quilombola children as a challenge for the Sustainable Development Goals: a scoping review - Emanuella Pereira de Lacerda; Sara Fiterman Lima; Bruno Luciano Carneiro Alves de Oliveira (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to map the literature on quilombola children’s health and its relationship with the Sustainable Development Goals. Method: a scoping review, which followed the JBI protocol and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. Searches were conducted in the LILACS, BDENF, Web of Science, Scopus, MEDLINE databases and Google Scholar platform. The research protocol was registered in the Open Science Framework. Results: eighteen articles out of 2,055 studies were selected as relevant for this study. The articles were grouped into four axes: Access to healthcare services; Nutritional aspects of quilombola children; Health problems of quilombola children; and Care for quilombola children. The relationship between these articles and SDGs 1, 3, 4, 6 and 10 was observed. Final considerations: the study provided an extremely important mapping of the theme of quilombola children’s health and themes related to the Sustainable Development Goals.